Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

Fungicide use patterns in South African barley production - M. M. Venter; S. I. Hull; C. Bester; P. A. Swanepoel (Journal of Plant Diseases and Protection, 2026)
Fungicide resistance is an escalating threat to barley ( Hordeum vulgare L.) production worldwide. To evaluate use patterns and potential resistance risks, fungicide application data from the South African national barley production traceability and compliance platform, called the Barley Passport (2021–2024) were analysed. Program intensity was consistently high, with three-application regimes dominating and two-application programs declining over time. Single-application programs were rare. Combinations of Succinate Dehydrogenase Inhibitors (SDHI) and Demethylation Inhibitors (DMI) represented the most common spray type (22–25% of fields), while mixtures of DMI, SDHI and Quinone outside Inhibitors (QoI) contributed an additional 15–22%. Together, SDHI-containing programs accounted for approximately 40–45% of all sprays annually. Spatial analysis revealed notable regional variation in fungicide application practices. Certain production regions consistently accounted for the highest number of treated barley fields, while other regions demonstrated a growing shift toward integrated fungicide programmes, particularly those combining SDHI + DMI and QoI chemistries. These patterns suggest differential responses to disease pressure, agronomic conditions, and resistance management awareness across the barley-growing landscape. Barley-on-barley cropping persisted on 20–21% of hectares, reinforcing conditions of elevated disease pressure. These findings show that South African barley production relies heavily on fungicide chemistries with a high risk of resistance development. This underscores the urgent need for integrated disease management and stewardship to preserve fungicide efficacy and ensure the long-term sustainability of the malting barley sector. Given barley’s global importance, insights into regional resistance dynamics and management responses in South Africa offer valuable lessons for international production systems facing similar challenges.

Poor transferability of richness models: Predicting plot-scale plant diversity in the Waterberg, South Africa - Tamryn S. Venter; Nigel P. Barker; Peter C. le Roux (South African Journal of Botany, 2024)

Prenatal exposure to poly- and perfluoroalkyl substances and the incidence of asthma in early childhood - Lauren M. Zell-Baran; Carina Venter; Dana Dabelea; Jill M. Norris; Deborah H. Glueck; John L. Adgate; Jared M. Brown; Antonia M. Calafat; Kaci Pickett-Nairne; Anne P. Starling (Environmental Research, 2023)

Genomic profiling of Pasteurella multocida isolated from feedlot cases of bovine respiratory disease - Tamara Alhamami; Piklu Roy Chowdhury; Henrietta Venter; Tania Veltman; Alec Truswell; Sam Abraham; Sylvia A. Sapula; Mandi Carr; Steven P. Djordjevic; Darren J. Trott (Veterinary Microbiology, 2023)

Description of two cultivated and two uncultivated new Salinibacter species, one named following the rules of the bacteriological code: Salinibacter grassmerensis sp. nov.; and three named following the rules of the SeqCode: Salinibacter pepae sp. nov., Salinibacter abyssi sp. nov., and Salinibacter pampae sp. nov. - Tomeu Viver; Roth E. Conrad; Marianna Lucio; Mourad Harir; Mercedes Urdiain; Juan F. Gago; Ana Suárez-Suárez; Esteban Bustos-Caparros; Rodrigo Sanchez-Martinez; Eva Mayol; Federico Fassetta; Jinfeng Pang; et al. (Systematic and Applied Microbiology, 2023)

Wilderness forms and their implications for global environmental policy and conservation - Katharina‐Victoria Pérez‐Hämmerle; Katie Moon; Rubén Venegas‐Li; Sean Maxwell; Jeremy S. Simmonds; Oscar Venter; Stephen T. Garnett; Hugh P. Possingham; James E. M. Watson (Conservation Biology, 2022)
With the intention of securing industry‐free land and seascapes, protecting wilderness entered international policy as a formal target for the first time in the zero draft of the Post‐2020 Global Biodiversity Framework under the Convention on Biological Diversity. Given this increased prominence in international policy, it is timely to consider the extent to which the construct of wilderness supports global conservation objectives. We evaluated the construct by overlaying recently updated cumulative human pressure maps that offer a global‐scale delineation of industry‐free land as wilderness with maps of carbon stock, species richness, and ground travel time from urban centers. Wilderness areas took variable forms in relation to carbon stock, species richness, and proximity to urban centers, where 10% of wilderness areas represented high carbon and species richness, 20% low carbon and species richness, and 3% high levels of remoteness (>48 h), carbon, and species richness. Approximately 35% of all remaining wilderness in 2013 was accessible in

Global human influence maps reveal clear opportunities in conserving Earth’s remaining intact terrestrial ecosystems - Jason Riggio; Jonathan E. M. Baillie; Steven Brumby; Erle Ellis; Christina M. Kennedy; James R. Oakleaf; Alex Tait; Therese Tepe; David M. Theobald; Oscar Venter; James E. M. Watson; Andrew P. Jacobson (Global Change Biology, 2020)
Leading up to the Convention on Biological Diversity Conference of the Parties 15, there is momentum around setting bold conservation targets. Yet, it remains unclear how much of Earth's land area remains without significant human influence and where this land is located. We compare four recent global maps of human influences across Earth's land, Anthromes, Global Human Modification, Human Footprint and Low Impact Areas, to answer these questions. Despite using various methodologies and data, these different spatial assessments independently estimate similar percentages of the Earth's terrestrial surface as having very low (20%–34%) and low (48%–56%) human influence. Three out of four spatial assessments agree on 46% of the non‐permanent ice‐ or snow‐covered land as having low human influence. However, much of the very low and low influence portions of the planet are comprised of cold (e.g., boreal forests, montane grasslands and tundra) or arid (e.g., deserts) landscapes. Only four biomes (boreal forests, deserts, temperate coniferous forests and tundra) have a majority of datasets agreeing that at least half of their area has very low human influence. More concerning, all datasets. These findings suggest that about half of Earth's terrestrial surface has relatively low human influence and offers opportunities for proactive conservation actions to retain the last intact ecosystems on the planet. However, though the relative abundance of ecosystem areas with low human influence varies widely by biome, conserving these last intact areas should be a high priority before they are completely lost.

The human footprint represents observable human pressures: Reply to Kennedy et al. - Oscar Venter; Hugh P. Possingham; James E. M. Watson (Global Change Biology, 2020)

National contributions to global ecosystem values - Laura E. Coristine; Sheila Colla; Nathan Bennett; Anja M. Carlsson; Christina Davy; Kimberley T.A. Davies; Brett Favaro; D.T. Tyler Flockhart; Kevin Fraser; Diane Orihel; Sarah P. Otto; Wendy Palen; et al. (Conservation Biology, 2019)
Current conservation templates prioritize biogeographic regions with high intensity ecosystem values, such as exceptional species richness or threat. Intensity‐based targets are an important consideration in global efforts, but they do not capture all available opportunities to conserve ecosystem values, including those that accrue in low intensity over large areas. We assess six globally‐significant ecosystem values—intact wilderness, freshwater availability, productive marine environments, breeding habitat for migratory wildlife, soil carbon storage, and latitudinal potential for range shift in the face of climate change—to highlight opportunities for high‐impact broadly‐distributed contributions to global conservation. Nations can serve as a cohesive block of policy that can profoundly influence conservation outcomes. Contributions to global ecosystem values that exceed what is predicted by a nation's area alone, can give rise to countries with the capacity to act as ‘conservation superpowers’, such as Canada and Russia. For these conservation superpowers, a relatively small number of national policies can have environmental repercussions for the rest of the world.

Size-resolved characteristics of inorganic ionic species in atmospheric aerosols at a regional background site on the South African Highveld - Andrew D. Venter; Pieter G. van Zyl; Johan P. Beukes; Jan-Stefan Swartz; Miroslav Josipovic; Ville Vakkari; Lauri Laakso; Markku Kulmala (Journal of Atmospheric Chemistry, 2018)

The extent and predictability of the biodiversity–carbon correlation - Moreno Di Marco; James E. M. Watson; David J. Currie; Hugh P. Possingham; Oscar Venter (Ecology Letters, 2018)
Protecting biomass carbon stocks to mitigate climate change has direct implications for biodiversity conservation. Yet, evidence that a positive association exists between carbon density and species richness is contrasting. Here, we test how this association varies (1) across spatial extents and (2) as a function of how strongly carbon and species richness depend on environmental variables. We found the correlation weakens when moving from larger extents, e.g. realms, to narrower extents, e.g. ecoregions. For ecoregions, a positive correlation emerges when both species richness and carbon density vary as functions of the same environmental variables (climate, soil, elevation). In 20% of tropical ecoregions, there are opportunities to pursue carbon conservation with direct biodiversity co‐benefits, while other ecoregions require careful planning for both species and carbon to avoid potentially perverse outcomes. The broad assumption of a linear relationship between carbon and biodiversity can lead to undesired outcomes.

Bias in protected‐area location and its effects on long‐term aspirations of biodiversity conventions - Oscar Venter; Ainhoa Magrach; Nick Outram; Carissa Joy Klein; Hugh P. Possingham; Moreno Di Marco; James E.M. Watson (Conservation Biology, 2018)
To contribute to the aspirations of recent international biodiversity conventions, protected areas (PAs) must be strategically located and not simply established on economically marginal lands as they have in the past. With refined international commitments under the Convention on Biological Diversity to target protected areas in places of “importance to biodiversity,” perhaps they may now be. We analyzed location biases in PAs globally over historic (pre‐2004) and recent periods. Specifically, we examined whether the location of protected areas are more closely associated with high concentrations of threatened vertebrate species or with areas of low agricultural opportunity costs. We found that both old and new protected areas did not target places with high concentrations of threatened vertebrate species. Instead, they appeared to be established in locations that minimize conflict with agriculturally suitable lands. This entrenchment of past trends has substantial implications for the contributions these protected areas are making to international commitments to conserve biodiversity. If protected‐area growth from 2004 to 2014 had strategically targeted unrepresented threatened vertebrates, >30 times more species (3086 or 2553 potential vs. 85 actual new species represented) would have been protected for the same area or the same cost as the actual expansion. With the land available for conservation declining, nations must urgently focus new protection on places that provide for the conservation outcomes outlined in international treaties.

Phylogenomic resolution of the bacterial genus Pantoea and its relationship with Erwinia and Tatumella - Marike Palmer; Emma T. Steenkamp; Martin P. A. Coetzee; Wai-Yin Chan; Elritha van Zyl; Pieter De Maayer; Teresa A. Coutinho; Jochen Blom; Theo H. M. Smits; Brion Duffy; Stephanus N. Venter (Antonie van Leeuwenhoek, 2017)

MALDI-TOF MS meets WGS in a VRE outbreak investigation - S. Schlebusch; G. R. Price; R. L. Gallagher; V. Horton-Szar; L. D. H. Elbourne; P. Griffin; D. J. Venter; S. O. Jensen; S. J. Van Hal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Bolder science needed now for protected areas - James E. M. Watson; Emily S. Darling; Oscar Venter; Martine Maron; Joe Walston; Hugh P. Possingham; Nigel Dudley; Marc Hockings; Megan Barnes; Thomas M. Brooks (Conservation Biology, 2016)
Recognizing that protected areas (PAs) are essential for effective biodiversity conservation action, the Convention on Biological Diversity established ambitious PA targets as part of the 2020 Strategic Plan for Biodiversity. Under the strategic goal to “improve the status of biodiversity by safeguarding ecosystems, species, and genetic diversity,” Target 11 aims to put 17% of terrestrial and 10% of marine regions under PA status by 2020. Additionally and crucially, these areas are required to be of particular importance for biodiversity and ecosystem services, effectively and equitably managed, ecologically representative, and well‐connected and to include “other effective area‐based conservation measures” (OECMs). Whereas the area‐based targets are explicit and measurable, the lack of guidance for what constitutes important and representative ; effective ; and OECMs is affecting how nations are implementing the target. There is a real risk that Target 11 may be achieved in terms of area while failing the overall strategic goal for which it is established because the areas are poorly located, inadequately managed, or based on unjustifiable inclusion of OECMs. We argue that the conservation science community can help establish ecologically sensible PA targets to help prioritize important biodiversity areas and achieve ecological representation; identify clear, comparable performance metrics of ecological effectiveness so progress toward these targets can be assessed; and identify metrics and report on the contribution OECMs make toward the target. By providing ecologically sensible targets and new performance metrics for measuring the effectiveness of both PAs and OECMs, the science community can actively ensure that the achievement of the required area in Target 11 is not simply an end in itself but generates genuine benefits for biodiversity.

The role of defensive ecological interactions in the evolution of conotoxins - J. R. Prashanth; S. Dutertre; A. H. Jin; V. Lavergne; B. Hamilton; F. C. Cardoso; J. Griffin; D. J. Venter; P. F. Alewood; R. J. Lewis (Molecular Ecology, 2016)
Venoms comprise of complex mixtures of peptides evolved for predation and defensive purposes. Remarkably, some carnivorous cone snails can inject two distinct venoms in response to predatory or defensive stimuli, providing a unique opportunity to study separately how different ecological pressures contribute to toxin diversification. Here, we report the extraordinary defensive strategy of the Rhizoconus subgenus of cone snails. The defensive venom from this worm‐hunting subgenus is unusually simple, almost exclusively composed of αD‐conotoxins instead of the ubiquitous αA‐conotoxins found in the more complex defensive venom of mollusc‐ and fish‐hunting cone snails. A similarly compartmentalized venom gland as those observed in the other dietary groups facilitates the deployment of this defensive venom. Transcriptomic analysis of a Conus vexillum venom gland revealed the αD‐conotoxins as the major transcripts, with lower amounts of 15 known and four new conotoxin superfamilies also detected with likely roles in prey capture. Our phylogenetic and molecular evolution analysis of the αD‐conotoxins from five subgenera of cone snails suggests they evolved episodically as part of a defensive strategy in the Rhizoconus subgenus. Thus, our results demonstrate an important role for defence in the evolution of conotoxins.

Size-resolved characterisation of organic compounds in atmospheric aerosols collected at Welgegund, South Africa - Wanda Booyens; Pieter G. Van Zyl; Johan P. Beukes; Jose Ruiz-Jimenez; Matias Kopperi; Marja-Liisa Riekkola; Miroslav Josipovic; Andrew D. Venter; Kerneels Jaars; Lauri Laakso; Ville Vakkari; Markku Kulmala; et al. (Journal of Atmospheric Chemistry, 2015)

Review of the Regulation of Veterinary Drugs and Residues in South Africa - R. R. Chanda; R. J. Fincham; P. Venter (Critical Reviews in Food Science and Nutrition, 2014)

Genetic characterization of bovine viral diarrhoea (BVD) viruses: confirmation of the presence of BVD genotype 2 in Africa - H. G. Ularamu; K. P. Sibeko; A. B. Bosman; E. H. Venter; M. van Vuuren (Archives of Virology, 2013)

Toxicity profile of commercially produced indigenous banana beer - K. Shale; J. Mukamugema; R.J. Lues; P. Venter (Food Additives & Contaminants: Part A, 2012)

Exotic species richness and native species endemism increase the impact of exotic species on islands - Jessica C. Walsh; Oscar Venter; James E. M. Watson; Richard A. Fuller; Tim M. Blackburn; Hugh P. Possingham (Global Ecology and Biogeography, 2012)
Aim Exotic species pose one of the most significant threats to biodiversity, especially on islands. The impacts of exotic species vary in severity among islands, yet little is known about what makes some islands more susceptible than others. Here we determine which characteristics of an island influence how severely exotic species affect its native biota. Location We studied 65 islands and archipelagos from around the world, ranging from latitude 65° N to 54° S. Methods We compiled a global database of 10 island characteristics for 65 islands and determined the relative importance of each characteristic in predicting the impact of exotic species using multivariate modelling and hierarchical partitioning. We defined the impact of exotic species as the number of bird, amphibian and mammal (BAM) species listed by the International Union for Conservation of Nature (IUCN) as threatened by exotics, relative to the total number of BAM species on that island. Results We found that the impact of exotic species is more severe on islands with more exotic species and a greater proportion of native species that are endemic. Unexpectedly, the level of anthropogenic disturbance did not influence an island's susceptibility to the impacts of exotic species. Main conclusions By coupling our results with studies on the introduction and establishment of exotic species, we conclude that colonization pressure, or invasion opportunities, influences all stages of the invasion process. However, species endemism, the other important factor determining the impact of exotic species, is not known to contribute to introduction and establishment success on islands. This demonstrates that different factors correlate with the initial stages of the invasion process and the subsequent impacts of those invaders, highlighting the importance of studying the impacts of exotic species directly. Our study helps identify islands that are at risk of impact by exotics and where investment should focus on preventing further invasions.

Time to detection of the growth of Mycobacterium tuberculosis in MGIT 960 for determining the early bactericidal activity of antituberculosis agents - A. H. Diacon; J. S. Maritz; A. Venter; P. D. Helden; K. Andries; D. F. McNeeley; P. R. Donald (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Avoiding Unintended Outcomes from REDD - Oscar Venter; James E.M. Watson; Erik Meijaard; William F. Laurance; Hugh P. Possingham (Conservation Biology, 2010)

Major Conservation Policy Issues for Biodiversity in Oceania - R. T. KINGSFORD; J. E. M. WATSON; C. J. LUNDQUIST; O. VENTER; L. HUGHES; E. L. JOHNSTON; J. ATHERTON; M. GAWEL; D. A. KEITH; B. G. MACKEY; C. MORLEY; H. P. POSSINGHAM; et al. (Conservation Biology, 2009)
Oceania is a diverse region encompassing Australia, Melanesia, Micronesia, New Zealand, and Polynesia, and it contains six of the world's 39 hotspots of diversity. It has a poor record for extinctions, particularly for birds on islands and mammals. Major causes include habitat loss and degradation, invasive species, and overexploitation. We identified six major threatening processes (habitat loss and degradation, invasive species, climate change, overexploitation, pollution, and disease) based on a comprehensive review of the literature and for each developed a set of conservation policies. Many policies reflect the urgent need to deal with the effects of burgeoning human populations (expected to increase significantly in the region) on biodiversity. There is considerable difference in resources for conservation, including people and available scientific information, which are heavily biased toward more developed countries in Oceania. Most scientific publications analyzed for four threats (habitat loss, invasive species, overexploitation, and pollution) are from developed countries: 88.6% of Web of Science publications were from Australia (53.7%), New Zealand (24.3%), and Hawaiian Islands (10.5%). Many island states have limited resources or expertise. Even countries that do (e.g., Australia, New Zealand) have ongoing and emerging significant challenges, particularly with the interactive effects of climate change. Oceania will require the implementation of effective policies for conservation if the region's poor record on extinctions is not to continue .

The influence of dose and N-acetyltransferase-2 (NAT2) genotype and phenotype on the pharmacokinetics and pharmacodynamics of isoniazid - P. R. Donald; D. P. Parkin; H. I. Seifart; H. S. Schaaf; P. D. van Helden; C. J. Werely; F. A. Sirgel; A. Venter; J. S. Maritz (European Journal of Clinical Pharmacology, 2007)

The pharmacological effects of ozone on isolated guinea pig tracheal preparations - C. J. Lotriet; D. W. Oliver; D. P. Venter (Archives of Toxicology, 2007)

Ascospore aggregation and oxylipin distribution in the yeast Dipodascopsis tothii - D.P. Smith; J.L.F. Kock; M.I. Motaung; P.W.J. van Wyk; P. Venter; D.J. Coetzee; S. Nigam (Antonie van Leeuwenhoek, 2000)

A novel oxylipin-associated ‘ghosting’ phenomenon in yeast flocculation - J.L.F. Kock; P. Venter; D.P. Smith; P.W.J. Van Wyk; P.J. Botes; D.J. Coetzee; C.H. Pohl; A. Botha; K-H. Riedel; S. Nigam (Antonie van Leeuwenhoek, 2000)

An acetylsalicylic acid-sensitive aggregation phenomenon in Dipodascopsis uninucleata - J.L.F. Kock; P.W.J. van Wyk; P. Venter; D.J. Coetzee; D.P. Smith; B.C. Viljoen; S. Nigam (Antonie van Leeuwenhoek, 1999)

Correlation between fusaric acid production and virulence of isolates ofFusarium oxysporum that causes potato dry rot in South Africa - Sonja L. Venter; P. J. Steyn (Potato Research, 1998)